Crosses between Journalism and Literature. An analysis of travel chronicles written by Juan Pablo Meneses - Lovato, Anahí (Anàlisi, 2011)
Journalism and Literature, as written devices, has in common their narrative nature, which is: the narration as a mode of telling, as a mode to convert chronological stories with their several perspectives and complex network of actions and speeches into text line. As autonomous fields, they hold characteristics that distance them and work as separatist limits. However, there are also closer characteristics between them that are revealed in experimental manifestations that we define as “crosses” between journalism and literature. Such characteristics can be recognized in travel chronicles written by Juan Pablo Meneses. Trying such recognition, the present article proposes an analysis of two of his texts based on concepts created by literature theory and journalism writing.